Evaluation of the Use of Postural Control Strategies during Dual-Tasks of Hearing-Impaired Athletes - Deniz Simsek; Caner Ozboke; Ela Arican Gultekin (Montenegrin Sports Academy, 2021)
Dual-tasks are often used with postural control. These tasks, which generally target motor skills and cognitive performance, also help to determine the individual's postural control. The purpose of this study is to determine the changes in performance during the motor task, which includes the cognitive cues of the hearing-impaired athletes. A total of 31 hearing-impaired athletes (male=19, female=12) and 34 hearing-impaired sedentary people (male=18, female=16) were included voluntarily in the study. The FitLight Trainer™ system was used to determine participants' reaction time levels. The performance time of hearing-impaired male athletes was significantly lower than the hearing-impaired sedentary men in each of the three tests (Random Test: t = 4, 089, p <0.05; Cue Test: t = 3,551, p <0.05; Mixed Cue Test: t = 2, 393, p<0.05). The performance time of hearing-impaired female athletes was statistically significantly lower than that of sedentary hearing-impaired females for all protocols (Random Test: t=2,586, p<0,05; Cue Test: t=2,568, p<0.05; Mixed Cue Test: t=2,899, p<0.05). This study demonstrates that 1) hearing-impaired athletes perform postural control adjustments automatically during the motor task, and they require minimal less cognitive effort than they need to be minimally considered; 2) regular physical activities and training showed a positive development on other systems, especially the proprioceptive system, which controls balance. In future studies, dual-task reaction time values and postural control strategy comparisons should be measured among hearing-impaired athletes and athletes who do not have a hearing disability.